1986
DOI: 10.1042/bj2380863
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal regulation of insulin secretion in the genetically obese (ob/ob) mouse

Abstract: To determine whether the abnormal insulin-secretory activity encountered in obese mice is due to an anomaly in the production of cyclic AMP, islets of lean and obese mice were incubated with forskolin under various conditions. Our data show that, in addition to the well-known quantitative differences in insulin-secretory activity between islets of lean and obese mice, there are important qualitative differences. The islets of obese mice accumulated less cyclic AMP than did those of lean mice in response to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
(48 reference statements)
2
8
0
Order By: Relevance
“…5B) were found to be increased in ob/ob islets as compared to CTL. As previously documented (Black et al, 1986;Fournier et al, 1990), we observed that insulin secretion was enhanced in islets from obese mice (Supplemental Fig. S4).…”
Section: Insulin Secretion and Exocytosis Are Increased In Ob/ob Pancsupporting
confidence: 71%
See 2 more Smart Citations
“…5B) were found to be increased in ob/ob islets as compared to CTL. As previously documented (Black et al, 1986;Fournier et al, 1990), we observed that insulin secretion was enhanced in islets from obese mice (Supplemental Fig. S4).…”
Section: Insulin Secretion and Exocytosis Are Increased In Ob/ob Pancsupporting
confidence: 71%
“…The increased insulin secretory capacity in ob/ob islets has been reported long time ago (Black et al, 1986;Fournier et al, 1990). Our capacitance experiments in intact islets demonstrate that this hypersecretion may be supported by an enhanced exocytotic capacity at the single cell level.…”
Section: Article In Pressmentioning
confidence: 56%
See 1 more Smart Citation
“…These studies were conducted in normal mouse or rat islets and demonstrated a glucose-regulated spermine content, suggesting a stimulatory or permissive role of spermine at multiple sites of insulin production and glucosesensitive insulin release, results reproduced in the present study. Such a role is also in conformity with the present observations of an increased spermine-tospermidine ratio in conjunction with a previously reported enhanced (pro)insulin biosynthesis (2) and hypersensitive secretory response to glucose (5,11,21,40) in islets of the obese-hyperglycemic mouse.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the traditional role of Gi/o proteins to block adenylate cyclase activity and reduce cAMP production, EP3γ activity may reduce NGOB β-cell cAMP levels from an even higher theoretical baseline. Numerous signaling changes have been demonstrated in β-cell compensation and failure, such as those mediated by β-cell stress pathways (6,9,38,39), many of which converge on cAMP (14,31,(40)(41)(42). In this scenario, EP3γ up-regulation may be a compensatory adaptation to dampen β-cell stress and promote β-cell survival.…”
Section: Discussionmentioning
confidence: 99%